ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN MURID KELAS III SD NEGERI 14/I SUNGAI BAUNG - Amna Ali; Ismi Luthfya Balqis; Selsha Juliana Dwi Putri; Khoirunnisa; Silvina Noviyanti (STKIP Subang, 2026)
This study aims to describe the reading comprehension ability of third-grade students at SDN 14/I Sungai Baung and to identify the factors that influence it. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and document analysis. The subjects of this study were 23 third-grade students and their classroom teacher. The results showed that the majority of students were at the medium category of reading comprehension ability, with only a small portion reaching the high category. Several students were still struggling with understanding the implicit meaning of texts, identifying the main idea of paragraphs, and retelling the content of readings in their own words. Factors that influenced students’ reading comprehension ability included students’ reading habits at home, family support, the teaching strategies used by the teacher and students’ vocabulary mastery. The findings of this study indicate the need for more varied and student-centered reading learning strategies to improve students’ reading comprehension skills in early grades of elementary school.